Selective Cooperative Transmission in Ad Hoc Networks with Directional Antennas. (25th November 2013) - Kim, Eui-Jik; Youm, Sungkwan
This paper presents a selective cooperative transmission scheme (abbreviated SCT) for ad hoc network with directional antennas that leverages the benefits of directional-only antenna approach and cooperative communication. The main feature of SCT is its adaptability to the channel condition in the network. In other words, when the node sends data, SCT determines its transmission strategy on either direct or cooperative transmission via a relay node called a forwarder, depending on the transmission time. Simulation results are provided to validate the effectiveness of the proposed scheme.